Kajian Strategik Manajemen Keamanan Siber terhadap Proyek Telematika di Indonesia: Studi Kasus Kebocoran Pusat Data Nasional - Ramadhani, Eka Hero; Enriko, I Ketut Agung; Sari, Erika Lety Istikhomah Puspita (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
On June 20, 2024, a cyber attack occurred on PDN, which caused several government public services in the form of SPBE to not run properly. The incident has the potential to cause data leakage and disclosure of the government and the Indonesian public by hackers. Cyber incident cases on PDN need to be studied in order to gain useful knowledge for implementing cybersecurity in telematics projects in Indonesia, especially SPBE. In this scientific paper, a study of cybersecurity management strategies is conducted on telematics projects in Indonesia with a case study of PDN leaks. The exploratory study method is used to identify the causes of cyber incidents on PDN. The factors causing PDN cyber incidents are then entered into the PPT framework to determine the handling solutions. The results of the identification and mapping show that there are 3 human factors, 4 factors, and 7 technological factors. The cybersecurity management strategy for telematics projects in Indonesia proposed in this study is in the form of solutions for handling, mitigating, and anticipating cyber incidents according to the case study studied. The results of this study can be a reference for organizers of public service telematics projects so that similar incidents do not occur in the future.